Brain Areas Specific for Attentional Load in a Motion-Tracking Task - Jovicich, Jorge; Peters, Robert J.; Koch, Christof; Braun, Jochen; Chang, Linda; Ernst, Thomas (Journal of cognitive neuroscience, 2001)
Although visual attention is known to modulate brain activity in the posterior parietal, prefrontal, and visual sensory areas, the unique roles of these areas in the control of attentional resources have remained unclear. Here, we report a dissociation in the response profiles of these areas. In a parametric functional magnetic resonance imaging (fMRI) study, subjects performed a covert motion-tracking task, in which we manipulated “attentional load” by varying the number of tracked balls. While strong effects of attention—independent of attentional load—were widespread, robust linear increases of brain activity with number of balls tracked were seen primarily in the posterior parietal areas, including the intraparietal sulcus (IPS) and superior parietal lobule (SPL). Thus, variations in attentional load revealed different response profiles in sensory areas as compared to control areas. Our results suggest a general role for posterior parietal areas in the deployment of visual attentional resources.